SUSTAINABLE PERFORMANCE AND FINANCIAL METRICS: THE IMPACT OF ESG SCORES ON PROFITABILITY AND MARKET VALUATION ON THE INDONESIA STOCK EXCHANGE - Rijal Habibulloh; Herry Achmad Buchory (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This research investigates how Environmental, Social, and Governance (ESG) Scores influence company profitability as measured by Earnings Per Share (EPS) with Market Valuation as measured by Price to Earnings Ratio (P/E Ratio) as a mediating variable. The study focuses on companies listed on the Indonesia Stock Exchange (IDX) in 2024 and utilizes path analysis to assess the interrelationships among the variables. The sample consists of all IDX-listed firms that report ESG Scores, selected through a total sampling approach. The findings indicate that ESG Scores significantly affect Market Valuation, suggesting that firms with higher ESG risk exposure tend to exhibit higher valuation multiples. Conversely, ESG Scores do not have a significant impact on Profitability, nor does Market Valuation influence Profitability. Furthermore, the mediation analysis reveals that Market Valuation does not mediate the relationship between ESG Scores and Profitability. This suggests that although ESG-related factors may elevate a company’s market valuation, they do not necessarily translate into improved financial performance. These results highlight the need for companies to align their sustainability initiatives with core operational strategies to achieve better financial outcomes. Additionally, this study provides important insights for investors and stakeholders by emphasizing the relevance of ESG considerations in evaluating corporate valuation and profitability.